Pengaruh Experiential Marketing Terhadap Loyalitas Tamu di Hotel Santika Depok (Studi Kasus di Era Pandemi Covid-19) - Sofiani Sofiani; Dessy Natalia; Felicia Tandi (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Hotel business has a high level of competition. According to Dicky Sumarsono, CEO of Azana Hotels & Resorts, competition in the hospitality business is getting tougher, so it is necessary to include an experience element to create a 'wow experience' and create excitement for guests. However, currently many businesses, including the hotel business, are facing a global challenge caused by the Covid-19 Pandemic. Hotel Santika Depok is one of the hotels that has experienced an impact, it caused a decrease in occupancy rates, even having to stop its operations for 2 months. The purpose of this study was to determine whether simultaneously and partially each of the dimensions sense, feel, think, act and relate in Experiential Marketing had a significant influence on Guest Loyalty at Hotel Santika Depok, with a case study in the Covid-19 Pandemic era. The theory used is according to Schmitt (1999), that experiential marketing has five elements, namely sense, feel, think, act and relate. Based on the results of the t test, it is known that the dimensions of think, act and relate have a significant effect on Guest Loyalty. Meanwhile, the sense and feel dimensions do not have a significant effect. Based on the results of the F test, it is known that the dimensions of the Experiential Marketing variable simultaneously have a significant influence on the Guest Loyalty variable. Based on the coefficient determination test, the r square result is 80%. Suggestions that can be given from this research are that room ventilation can be paid more attention so that it does not cause unpleasant odors, creates a better atmosphere and service so that guests can get a better mood, increase the ability to deal with guest complaints, including in aspects speed and solutions provided, and also adding activities such as holding social and cultural activities so that guests can be more interested in participating.